An Engineered Mouse to Identify Proliferating Cells and Their Derivatives - Jang, Jihyun; Engleka, Kurt A.; Liu, Feiyan; Li, Li; Song, Guang; Epstein, Jonathan A.; Li, Deqiang (Frontiers in Cell and Developmental Biology, 2020)
Background: Cell proliferation is a fundamental event during development, disease, and regeneration. Effectively tracking and quantifying proliferating cells and their derivatives is critical for addressing many research questions. Cell cycle expression such as for Ki67, proliferating cell nuclear antigen (PCNA), or aurora kinase B (Aurkb), or measurement of 5-bromo-2'-deoxyuridine (BrdU) or 3H-thymidine incorporation have been widely used to assess and quantify cell proliferation. These are powerful tools for detecting actively proliferating cells, but they do not identify cell populations derived from proliferating progenitors over time. Aims: We developed a new mouse tool for lineage tracing of proliferating cells by targeting the Aurkb allele. Results: In quiescent cells or cells arrested at G1/S, little or no Aurkb mRNA is detectable. In cycling cells, Aurkb transcripts are detectable at G2 and become undetectable by telophase. These findings suggest that Aurkb transcription is restricted to proliferating cells and is tightly coupled to cell proliferation. Accordingly, we generated an AurkbER Cre/+ mouse by targeting a tamoxifen inducible Cre cassette into the start codon of Aurkb. We find that the AurkbER Cre/+ mouse faithfully labels proliferating cells in developing embryos and regenerative adult tissues such as intestine but does not label quiescent cells such as post-mitotic neurons. Conclusions: The AurkbER Cre/+ mouse faithfully labels proliferating cells and their derivatives in developing embryos and regenerative adult tissues. This new mouse tool provides a novel genetic tracing capability for studying tissue proliferation and regeneration.